Feedback Valence Agency Moderates the Effect of Pre-service Teachers’ Growth Mindset on the Relation Between Revising and Performance - Cutumisu, Maria (Frontiers in Psychology, 2019)
It is often assumed that having a choice in the learning process may benefit performance and learning. Concomitantly, it is believed that learning choices (e.g., seeking critical or confirmatory feedback) are due to mindset. However, the relation between choices and mindset is still a matter of debate: it is not known whether mindset interferes with the decision to seek critical feedback, the response to critical feedback, or both. This experiment investigates for the first time whether feedback valence agency moderates the effect of mindset on the relation between learning behaviors and learning outcomes. Participants were n = 120 pre-service teachers who were randomly assigned to one of two conditions, Choose (n = 68) and Assign (n = 52), and designed three posters in Posterlet, a game that assessed their learning behaviors (critical feedback and revising) and poster performance. Then, they completed a learning post-test that also included a mindset survey. Results reveal similar non-significant correlation patterns of mindset with learning behaviors and learning outcomes in both conditions. Feedback valence agency (i.e., condition) moderates the effect of growth mindset on the relation between revision and performance: students who choose to revise their posters more often (i.e., at least twice) perform significantly better when they endorse higher rather than lower levels of growth mindset but only when feedback valence is chosen rather than assigned. Theoretical implications indicate that feedback valence agency moderates the effect of growth mindset in driving how students respond to their own learning choices to improve their performance.